Physical mechanisms, dynamics and interconnections of multiple estuarine turbidity maximum in the Pearl River estuary - Ma, Mengyao; Porz, Lucas; Schrum, Corinna; Zhang, Wenyan (Frontiers in Marine Science, 2024)
The formation and dynamics of individual estuarine turbidity maximum (ETM) in the Pearl River estuary (PRE) have been investigated but the temporal variability of the ETMs and interconnections among them remain poorly understood. To address these open questions, the distribution and transport of suspended particulate matter (SPM) in the PRE for the period of 2017–2020 are investigated by numerical modeling. The simulated sediment transport flux is decomposed into several major components associated with specific physical processes. Then, the relative contribution of each component to the formation of the ETMs is evaluated. Results suggest the coexistence of three prominent ETMs in the Lingding Bay of the PRE. They are formed by different physical mechanisms and characterized by remarkable seasonality in the spatial extension. In the two ETMs located at the west shoal and middle shoal, advection dominates the sediment transport flux, whilst tidal pumping plays a crucial role in maintaining the ETMs. A sharp bathymetric gradient leads to an entrapment of sediment flux within the bottom layer in the west channel ETM, a phenomenon referred to as topographical trapping. The interconnection analysis shows that the sediment transport between the ETMs varies with seasons, which is attributed to the variation of stratification driven by the monsoon-mediated river runoff. Our results provide new insights into the physical dynamics and interconnections of the ETMs in the PRE, which can serve as scientific base for estuarine sediment management and engineering.